Pengaplikasian Sistem Informasi Aplikasi Pencatatan Informasi Akuntansi (SiAPik) Pada UMKM Mama Mili Surabaya - Setyawati, Vincentia Devina; Tresyanto, Citra Anggraini; Halan, Yohanes Fabiyola (Universitas Negeri Gorontalo, 2025)
In the food and beverage sales sector, these challenges become increasingly complex due to the high dynamics of transactions, such as purchasing raw materials, recording daily income, and managing profits. Based on previous research, many food and beverage SME's still rely on manual record-keeping or do not record their transactions at all. The lack of understanding and skills in using modern financial recording systems is one of the main factors. In today's digital era, the use of information technology, such as simple and user-friendly financial recording applications, can be a solution. However, adopting such technology requires education and guidance for SME's practitioners to enable them to utilize it optimally. The method applied in this community service was implemented at one of the SME's in Surabaya, namely Mama Mili SME's, which sells food and beverages offline. Training on the application of the system was conducted through the SiAPik application. Mama Mili SME's greatly benefited from recording its sales transactions, with the simplest advantage being the calculation of profits from product sales.